Associação mãos que se ajudam: desenvolvimento sustentável e empoderamento de mulheres artesãs do Município de Lucena-PB - Azevedo, Patricia Morais de (2018)
The relationship between women empowerment and sustainable development is one of the most debated themes in the current context, bringing to the discussion categories of analysis such as equity, freedom, labor market, family relationships, environmental preservation, development, sustainability, involving scenarios of the world of female labor and which have been the subject of analysis. The achievements of women, from the 1960´s, have given them greater autonomy and confidence in the search for their goals, many of them related to the work done with natural resources. This thesis aims to analyze the process of women artisans empowerment for sustainable development, based on the experience of the group that forms the Mãos que se Ajudam Association in the Municipality of Lucena / PB. In order to do so, it was necessary to carry out the following specific objectives: evaluate the social capital accumulated by women who are part of the Mãos que se Ajudam Association and their self-managing capacity; to characterize the relationships of women artisans in their productive practices; and to rebuild the memory of the organization process of the Mãos que se Ajudam Association, through the identification of its leaders, the behaviors of the people who integrate it, its system of rules, the ways of exercising power. The research methodology, mainly qualitative, consisted of a combination of several approaches, starting with documentary and bibliographic research, followed by field research, in which data were collected through interviews with the last presidents of the Association, with the managers of the incentive bodies, as well as questionnaires applied to other members. It was also used the technique of the life trajectory of one of the artisans in a prominent position in the Association, which was revealed as a leadership, aiming to evaluate the process of individual and collective empowerment. An ethnographic research was carried out with participant observation in the kitchen among the cocada (coconut sweet) makers, involving the researcher in the preparation of cocada. The work consists of a theoretical foundation addressing the guiding themes of this research. As result, it was found that the empowerment of women artisans from the Mãos que se Ajudam Association is still in the process of development. They revealed through their experience in the Association that they have personal, relational and collective empowerment types, but they still need to work on their associativist culture. On the other hand, although they have used social capital in the formation of this Association, it has not yet contributed to a learning that leads to a more efficient self-management. With the third President, the first to be elected by women artisans, there is a prospect that the self-management process will happen and therefore the empowerment of women will be established definitely.